2014
DOI: 10.1088/0022-3727/47/43/432001
|View full text |Cite
|
Sign up to set email alerts
|

Electron properties in an atmospheric helium plasma jet determined by Thomson scattering

Abstract: In this work we present Thomson scattering measurements on a nanosecond pulsed high voltage dielectric barrier discharge (DBD)-like helium plasma jet, operated in ambient air. With the low detection limit offered by a triple grating spectrograph equipped with a high quantum efficiency intensified charge-coupled device (ICCD) camera, temporally and spatially resolved electron densities and mean energies have been mapped. 7 kV peak with 250 ns width pulses at 20 kHz are applied to the inner cylindrical shaped el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 24 publications
12
62
1
Order By: Relevance
“…This leads to typical order of magnitude for the ionization degree of 10 −7 , emphasising strong differences in comparison with low pressure discharges. These values are in general underestimated in comparison with other measurements such as Stark broadening of hydrogen lines [54], Thomson scattering of laser radiation [55,56] or Rayleigh microwave scattering [57], mainly due to difficulty of finding correct values for drift velocity. Although the electron density estimation from plasma column current monitoring is only a rough method, other issues related mainly to experimental design of the plasma sources must be considered in order to compare experimental results.…”
Section: Plasma Source Quasi-stationary Working Regimementioning
confidence: 80%
“…This leads to typical order of magnitude for the ionization degree of 10 −7 , emphasising strong differences in comparison with low pressure discharges. These values are in general underestimated in comparison with other measurements such as Stark broadening of hydrogen lines [54], Thomson scattering of laser radiation [55,56] or Rayleigh microwave scattering [57], mainly due to difficulty of finding correct values for drift velocity. Although the electron density estimation from plasma column current monitoring is only a rough method, other issues related mainly to experimental design of the plasma sources must be considered in order to compare experimental results.…”
Section: Plasma Source Quasi-stationary Working Regimementioning
confidence: 80%
“…Already the first observation [3] of plasma bullets-streamers guided along the jet axis-revealed a ring profile of their radiation, with maximum of radiation intensity shifted from the axis. In the following works, ring profiles of various radiating states [4]- [12], metastable helium atoms [13], and electrons [14] in helium plasma jets have been observed. Such profiles have been obtained also in simulations of streamers propagating along thin channels of pure helium [15]- [17] and along helium jets (with account of mixing of helium with ambient air) [18]- [20].…”
Section: Introductionmentioning
confidence: 98%
“…Babaeva and Kushner showed that streamer always first develops as a single filament propagating along the axis similar to conventional streamers in unconfined gases. Then depending on the dielectric constant of the surrounding media, the surface‐hugging streamer will, and will not, suppress the development of the axial streamer . For our experiments, the consistent appearance of axial mode suggests in case (a) that the electric field along the center line plays the dominant role.…”
Section: Resultsmentioning
confidence: 65%
“…Electrical discharges in or on liquid surface have attracted much attention during recent years, due to their applications in areas such as medical treatment, environmental mediation, and material synthesis . Comparing with discharges in air, direct ignition of plasma in liquid requires much higher threshold electric field.…”
Section: Introductionmentioning
confidence: 99%